2006
DOI: 10.1039/b517069a
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric induction during electron transfer mediated photoreduction of carbonyl compounds: role of zeolites

Abstract: Photochemistry of 17 aryl alkyl ketones included within cation exchanged zeolites has been examined. In solution five of the 17 ketones undergo intramolecular hydrogen abstraction reaction even in the presence of a chiral amine and the rest are photoreduced to the corresponding alcohol. Within zeolites all 17 ketones yielded in presence of a chiral amine, the corresponding alcohol as the major product. When a chiral amine was used as the coadsorbent within alkali ion exchanged zeolites, enantiomerically enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Our computational and solidstate NMR results in the case of phenyl cyclohexyl ketones were recently presented. 33 In this example, we showed that the alkali ion enforces an interaction between the chiral inductor and the ketone. We believe that the same phenomenon plays a role in aoxoamides as well.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our computational and solidstate NMR results in the case of phenyl cyclohexyl ketones were recently presented. 33 In this example, we showed that the alkali ion enforces an interaction between the chiral inductor and the ketone. We believe that the same phenomenon plays a role in aoxoamides as well.…”
Section: Discussionmentioning
confidence: 86%
“…During the last decade, we have provided several examples in which enantioand diastereoselectivities were obtained in zeolites but not in solution. [32][33][34][35][36][37][38][39] Recognizing the lack of availability of chiral zeolites, we have modified the interior of an achiral zeolite by adsorbing optically pure chiral inductors. In another approach, we employed covalently linked chiral auxiliaries to bring about chiral induction in photoreactions.…”
Section: Introductionmentioning
confidence: 99%
“…This choice restricts the reaction to cage A in Figure 2. To fulfill this criterion, we chose an amine-induced photoreduction of carbonyl compounds (Scheme 1) [56,57,58]. This reaction is prompted by an electron transfer from amine to an excited ketone.…”
Section: Chiral Inductor As An Active Co-guest: Photoreduction Promentioning
confidence: 99%
“…The role of the cation is likely to immobilize the substrate either by cation-π interactions or by cation-dipolar interactions with nitro or carbonyl groups. Work is still ongoing to improve both the generality and predictability of asymmetric induction in zeolites [136][137][138].…”
Section: Intrazeolite Asymmetric Photoreactionsmentioning
confidence: 99%